Determinants of health seeking behavior for chronic non-communicable diseases and related out-of-pocket expenditure: results from a cross-sectional survey in northern Bangladesh - Rasul, Fatema; Kalmus, Olivier; Sarker, Malabika; Adib, Hossain Ishrath; Hossain, Md Shahadath; Hasan, Md Zabir; Brenner, Stephan; Nazneen, Shaila; Islam, Muhammed Nazmul; De Allegri, Manuela (Journal of health, population and nutrition, 2019)
In spite of high prevalence rates, little is known about health seeking and related expenditure for chronic non-communicable diseases in low-income countries. We assessed relevant patterns of health seeking and related out-of-pocket expenditure in Bangladesh.
Gesehen am 01.04.2020